Faktor-Faktor yang Berhubungan dengan Perilaku Pemilihan Makanan Jajanan pada Siswa MI Sudirman Kawengen 01 - Vanny Verawati; Herry Susanto; Indra Tri Astuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Elementary school children are vulnerable to choosing unsafe snacks because they tend to prioritize appearance and taste over nutritional safety. Snack food selection behavior is influenced by various internal factors, such as knowledge and attitude, as well as external factors, including allowance, the habit of bringing lunch, and breakfast habits. Objective o determine factors associated with snack food selection behavior among students in grades 3–6 at MI Sudirman Kawengen 01. This study employed a cross-sectional design with a total sampling technique involving 106 students from grades 3–6. Data were collected using validated questionnaires covering variables of knowledge, attitude, allowance, the habit of bringing lunch, and breakfast habits. Bivariate analysis was conducted using the Chi-square test, while multivariate analysis used logistic regression with a significance level of p<0.05. Result most respondents were 10 years old (30.2%), male (50.9%), and predominantly in grade 5 (30.2%). Knowledge (p=0.001), attitude (p=0.001), and breakfast habits (p=0.001) were significantly associated with snack food selection behavior. Meanwhile, allowance (p=0.068) and the habit of bringing lunch (p=0.593) were not significantly associated. Multivariate analysis showed that no variable had a significant influence on snack food selection behavior. Conclusion knowledge, attitude, and breakfast habits are associated with snack food selection behavior among elementary school students.